Visual Form Generation: Optimizing Creativity Vis-A-Vis Hurlburtas Model (Global Journal of Human-Social Science, 2016)
Creativity the generation of new ideas and forms that provide valuable solution to a given problem often from an existing idea knowledge and object is indispensable in form generation It determines to a large extent the aesthetic and functional products the artist and designer produce that immensely impact on our everyday lives A key challenge facing the artist and designer is how to use understanding of the creative process albeit adocumented process with prevalent unawareness to optimize creativity in the course of form generation Therefore this paper focuses on how to optimize creativity in the process of generating visual form using Hurlburt s model of the creative process It employed qualitative research method which utilized the Critical-Historical-Analytic examination and Content Analysis The paper introduced the reader to the need for optimizing creativity in order to generate aesthetic and functional visual forms Also it thoroughly examined the creative process that affords visual forms Furthermore the paper showed how creativity was employed to explore combine and transform past and existing forms into new aesthetic and functional products
Keywords: visual task resolution; problem-solving process; form-generation process; creative process; tangible product